The Potential of Chitosan and Virgin Coconut Oil as Egg Coating Materials to Maintain the Quality of Local Duck Eggs during Storage - Eli Sahara; Febrinita Ulfah; Sofia Sandi; Muhakka; Andi Mushawir (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2026)
Eggs can be preserved by soaking them in an antibacterial solution. Chitosan and pure coconut oil are two such materials. This study aimed to extend the shelf life of eggs while maintaining their quality. The present study applied a completely randomized design (CRD) with five treatments and four. The eggs were stored for 14 days under room temperature (25-30◦C) and 70-80% relative humidity. The treatments in this study were: P0 = without a chitosan solution and coconut oil, P1 = soaked in a 1% chitosan solution, P2 = soaked in a 2% chitosan solution, P3 = soaked in a 3% chitosan solution, and P4 = soaked in a 100% coconut oil solution. The observed variables were egg weight loss, albumen and yolk weight. The results showed that the treatments significantly affected weight loss and albumen weight (P<0.05) but not yolk weight (P>0.05). Soaking eggs in 100% coconut oil (P4) resulted in the lowest weight loss (1.26%), which was significantly different from chitosan treatments (1-3%) and the control (2.66%). Similarly, the highest albumen weight (43.98%) was found in the coconut oil treatment. The treatments also showed no significant effect on the albumen and yolk index, as well as the pH of albumen and yolk. Treatment using coconut oil showed the best results in maintaining the internal quality of duck eggs with the smallest weight loss of 1.26% and maintaining the largest albumen weight of 43.98%. The treatment also showed no significant effect on albumen index, yolk index, pH of albumen and yolk. In conclusion, coconut oil effectively maintained egg quality, while chitosan was less effective.